The acquisitiveness of youth: CEO age and acquisition behavior - Yim, Soojin (Journal of Financial Economics, 2013)
I demonstrate that acquisitions are accompanied by large, permanent increases in Chief Executive Officer (CEO) compensation, which create strong financial incentives for CEOs to pursue acquisitions earlier in their career. Accordingly, I document that a firm's acquisition propensity is decreasing in the age of its CEO: a firm with a CEO who is 20 years older is ∼30% less likely to announce an acquisition. This negative effect of CEO age on acquisitions is strongest among firms where CEOs likely anticipate or can influence high post-acquisition compensation, and is absent for other investment decisions that are not rewarded with permanent compensation gains. The age effect cannot be explained by the selection of young CEOs by acquisition-prone firms, nor by a story of declining overconfidence with age. This paper underscores the relevance of CEO personal characteristics and CEO-level variation in agency problems for corporate decisions.